Influence of potassium fertilization and borácica performance Sunflower - Feitosa, Hernandes de Oliveira; FARIAS, GABRIEL CASTRO; Silva Junior, Ricardo José costa; ferreira, Francisco jardelson; Andrade Filho, Francisco Luciano; Lacerda, Claudivan Feitosa (Comunicata Scientiae, 2013)
The sunflower is presented as a promising crop for biodiesel production, in addition, to provideimproved soil fertility by having a high capacity for nutrient cycling absorbed in depth and a reducedrate of nutrient export, but it is very demanding on nutrients as boron and potassium. Therefore,we evaluated the effect of fertilization borácica and potassium in sunflower farming Catissol. Theexperimental design was a randomized complete block in a split-plot, 5 x 4 with five repetitions. Thetreatments consisted of a combination of five doses of boron (0, 2, 4, 6 and 8 kg ha-1), with four levelsof potassium (0, 30, 60 and 90 kg ha-1). Plants were harvested at 72 days after sowing and wereevaluated for height, leaf area, dry biomass and productivity. Doses of 6 and 90 kg ha-1 of boron andpotassium, respectively, provided better responses in height (190 cm), leaf area (4374 cm2), shootdry biomass (175 g) and productivity of 4170 kg ha-1.